2018
DOI: 10.1016/j.jacbts.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Strikingly Different Atheroprotective Effects of Apolipoprotein A-I in Early- Versus Late-Stage Atherosclerosis

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Cumulatively, the findings from Morton et al. (11) support the concept of a functional loss of vasoprotective properties of apoA-I and HDL under advanced age and diseased milieu conditions. Of note, a recent report demonstrated that accumulated apoA-I in human atheromas is largely dysfunctional due to extensive oxidation by myeloperoxidase with subsequently impaired ABCA1-dependent cholesterol acceptor activity (14) .…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Cumulatively, the findings from Morton et al. (11) support the concept of a functional loss of vasoprotective properties of apoA-I and HDL under advanced age and diseased milieu conditions. Of note, a recent report demonstrated that accumulated apoA-I in human atheromas is largely dysfunctional due to extensive oxidation by myeloperoxidase with subsequently impaired ABCA1-dependent cholesterol acceptor activity (14) .…”
mentioning
confidence: 79%
“…The findings from Morton et al. (11) are of particular clinical interest in light of therapeutic strategies to selectively raise apoA1. Such strategies have already been tested, for example, with the agent RVX-208 in the ASSERT trial (Efficacy and Safety of a Novel Oral Inducer of Apolipoprotein A-I Synthesis in Statin-Treated Patients With Stable Coronary Artery Disease), although it failed to achieve a significant change in plaque regression in patients with coronary disease as assessed by intravascular ultrasound imaging (16) .…”
Section: Clinical Relevance Of Experimental Findings and Future Perspmentioning
confidence: 98%
See 2 more Smart Citations
“…Apolipoprotein a1 (ApoA1) is the main component of HDL, and it may affect the anti-inflammatory and anti-oxidative effects of HDL via various mechanisms [10]. A large number of animal studies confirmed that high ApoAI expression reduced the volume of atherosclerotic plaques [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%